2019
DOI: 10.1038/s41598-019-49738-1
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperfusion leads to impairment in hemostasis and coagulation process in patients with acute pesticide intoxication

Abstract: Hemoperfusion (HP) is one of the important treatment modalities in extracorporeal therapy for patients with acute intoxication. Its use has declined during the past 20 years despite its efficacy, because of its side effects, especially an increased risk of bleeding. Mechanisms of hemostasis impairment have not been clearly elucidated and studies demonstrating the mechanism are lacking. It is not clear which step of the hemostatic process is impaired during HP, and whether it leads to an increased risk of bleed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…However, neither the exact effect of cholinergic substances on megakaryocyte formation nor the receptors that may mediate these effects have been identified [ 20 ]. Also, in another study, it has been reported that in patients with acute pesticide poisoning, hemoperfusion caused impaired platelet aggregation with incomplete platelet activation, which was associated with decreased thrombin formation with increased fibrinolysis [ 21 ]. Al-Sarar et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither the exact effect of cholinergic substances on megakaryocyte formation nor the receptors that may mediate these effects have been identified [ 20 ]. Also, in another study, it has been reported that in patients with acute pesticide poisoning, hemoperfusion caused impaired platelet aggregation with incomplete platelet activation, which was associated with decreased thrombin formation with increased fibrinolysis [ 21 ]. Al-Sarar et al.…”
Section: Discussionmentioning
confidence: 99%
“…Early hemoperfusion approaches to treat intoxication with modified charcoal have been reported to have undesirable effects on hemostasis and coagulation activity leading to their disuse 45 . In contrast, longer-term clinical studies (30-& 60-day) have established CS treatment to be safe and effective for a number of indications in critically ill patients 46 easing general concerns about disturbances to physiologic homeostasis through untoward removal of beneficial substances, however close drug level monitoring is essential as some antibiotics and other drugs are known to be adsorbed 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Another side effect observed in hemoperfusion is thrombocytopenia. Hemoperfusion has been shown to significantly decrease platelet count and impair coagulation due to direct binding to the absorbent surface or the activation of complement system [ 48 ]. Thrombocytopenia is also observed in plasmapheresis and is most common in centrifugation‐based apheresis and the use of albumin as replacement solution [ 42 ].…”
Section: Discussionmentioning
confidence: 99%